The Expressions of Indonesian Muslims in Performing the ʿUmrah Pilgrimage to Mecca - Dewi, Subkhani Kusuma (Universitas Islam Internasional Indonesia, 2023)
Minor Islamic pilgrimages (ʿumrah) are increasingly being studied as part of commodified pilgrimages in the age of trade and tourism. This relatively modern construction has restricted researchers’ understandings of practices like pilgrimages to the graves of saints. This article compares two imagined Indonesian Muslim religio-cultural communities performing ʿumrah, utilizing a hybrid ethnography method to obtain data. The paper is structured in two sections. Firstly, it discusses how traditionalist Muslims understand ʿumrah as a means of maintaining the authority of the teachings of Sufi ʿulamāʾ. This group adopts the ethical principles of Sufi practices, which involve three key elements: reverence for Sufi ʿulamāʾ, observance of sacred times, and the recitation of prayers to obtain intercession (shafāʿah) and blessings in life (barākah). The second section explores how another group, guided by Muslim ethics, aligns ʿumrah journeys with the principles of capitalism within Islam. Using global and cosmopolitan Muslim perspectives, these spiritual reformers and coaches approach ʿumrah by creating practices suitable for the aspirations of the middle-class Muslims. They tailor the practice of ʿumrah, based on Islamic practices, to account for the ethical principles of self-managing individuals. This comparative presentation demonstrates diverse Muslim experiences, refraining from a homogenous expression of the ʿumrah. Ultimately, this paper advocates for more comprehensive studies of the ʿumrah pilgrimage in Indonesia, including ones that focus on nuanced expressions of pilgrims and diverse roles played by Islamic religious authorities, moving beyond simplified commercial interpretations.